Expanding the aqueous-based redox-facilitated self-polymerization chemistry of catecholamines to 5, 6-dihydroxy-1H-benzimidazole and its 2-substituted derivatives. Issue 30 (7th March 2016) - Fan, Ka Wai; Peterson, Matthew B.; Ellersdorfer, Peter; Granville, Anthony M.
Abstract : Redox-facilitated self-polymerization can be performed with 5, 6-dihydroxy-1 H -benzimidazole to generate materials analogous to polydopamine, proving the possibility to expand the catecholamine-based chemistry to N-heterocyclic catechol derivatives. Abstract : Aqueous-base redox-facilitated self-polymerization can be performed with 5, 6-dihydroxy-1 H -benzimidazole (DHBI) to generate polymeric material that is analogous to poly(dopamine) (PDA), proving the possibility to expand the catecholamine-exclusive chemistry to N-heterocyclic catechol derivatives. DHBI underwent similar reaction pathways as dopamine to self-polymerize into the lightly cross-linked, π-conjugated poly(5, 6-dihydroxy-1 H -benzimidazole) (PDHBI). However, it was observed that the polymerization of DHBI proceeded faster than dopamine, and can be further enhanced under UV-stimulation, similar to dopamine polymerization. When coated on various substrates, the PDHBI coatings were capable of promoting surface wettability similar to PDA, but exhibited lower thermal stability due to a reduced cross-link density. Copolymerization compatibility between DHBI and dopamine was demonstrated, and it was possible to enhance the thermal stability of PDHBI by incorporating dopamine as a comonomer/cross-linker. Despite the high level of similarity between the two polymers, PDHBI possesses the imidazole moieties as unique features. Because of the versatile chemistry of o -benzenediamine employed for the monomer synthesis, DHBI-based monomers with specific functionality at the 2-carbon position of the imidazole ring can be prepared by choosing a desirable carboxylic acid. Two 2-substituted derivatives of DHBI were synthesized to demonstrate the ability to intrinsically modify the properties of PDHBI-based polymeric materials in terms of solubility, structure, and thermal stability.